COVID-19 and Alcohol Misuse: A Case Report - Asadollahi-Amin, Ali; Nowroozi, Ali; Hasibi, Mehrdad; Asanjarani, Behzad; SeyedAlinaghi, SeyedAhmad (Infectious Disorders - Drug Targets, 2021)
At the beginning of 2020, a newly emerged virus, now named SARS-CoV-2, began to spread in China. After four months, it has reached all over the globe, infecting more than 2.5 million people. Currently, there are no proved treatments available. However, in social media, false information about alcohol consumption and its role against the virus is spreading. We described a victim of these false facts, who was present with reduced eyesight due to alcohol drinking. A few days later, he showed symptoms of COVID-19 and, even though received treatment, lost his eyesight partially. Alcohol taking has no preventive or curative effect on COVID-19 and negatively impacts the body and immune system, which, therefore, should not be considered a treatment for COVID-19 disease.
Keywords: alcohol misuse